Students' Perceptions of English Learning in Islamic Boarding School: A Case Study - M Ilyas; Budik Kusworo (International Journal on Advanced Science, Education, and Religion, 2026)
This study explores students’ perceptions of English language learning at Raudlatul Ulum 2 Islamic Boarding School, examining its position within the curriculum, the challenges students face, and the factors influencing their motivation. Using a qualitative case study approach, data were collected through surveys, semi-structured interviews, and classroom observations and analysed thematically. The findings show that while students recognize English as a strategic skill for accessing global knowledge, higher education, international communication, and career opportunities, it remains secondary to the Islamic boarding school’s primary focus on Islamic sciences and Arabic due to curriculum priorities, limited teaching resources, and less engaging instructional methods. Despite these institutional constraints, students demonstrate high internal motivation, particularly driven by aspirations for higher education and global engagement, and view English as a tool for preaching and disseminating Islamic values, indicating that religious principles support rather than hinder language learning. The study also highlights the potential of innovative, student-centred methods—such as interactive games, digital-assisted instruction, and contextualized projects—to increase engagement, enhance language competence, and integrate English into daily practice. These findings suggest that with systemic support, culturally sensitive, and contextually relevant programs, English learning in Islamic boarding school can become a strategic competence that aligns with students’ academic, professional, and spiritual development.